2019
DOI: 10.1080/24733938.2019.1665704
|View full text |Cite
|
Sign up to set email alerts
|

Psychological momentum in football: the impact of a last-minute equalizer in a knock-out match

Abstract: What could be the impact of a last-minute equalizer on players' psychological momentum (PM) in a highstake, knockout football match? In the current study, 86 competitive male players were asked to imagine that they were playing in a cup final in which they were trailing 1-0 or leading 1-0. Subsequently, participants watched a video clip in which their team or the opponent team scored the equalizer either in the 61 st minute or 92 nd minute (i.e., last-minute) of regular playing time. Participants indicated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These two matches were chosen because in each of them, (a) a team gained an advantage and then saw that advantage grow rapidly (+2, +3, and/or +4) before being caught up and overtaken, and (b) the other team's comeback and equalizer took place well before the end of the match. This choice of a comeback far from the end of the match was made to avoid introducing a second type of momentum specific to the end-of-match context (Den Hartigh et al, 2020). A positive or negative momentum phase corresponded to a series of consecutive goals scored or conceded, respectively (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two matches were chosen because in each of them, (a) a team gained an advantage and then saw that advantage grow rapidly (+2, +3, and/or +4) before being caught up and overtaken, and (b) the other team's comeback and equalizer took place well before the end of the match. This choice of a comeback far from the end of the match was made to avoid introducing a second type of momentum specific to the end-of-match context (Den Hartigh et al, 2020). A positive or negative momentum phase corresponded to a series of consecutive goals scored or conceded, respectively (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Among the precipitation of events identified as momentum triggers in sport, one of the most often cited by athletes or coaches is how rapidly or decisively the score evolves-in point-or goal-counting sports-or more generally the increase or decrease of distance from victory (Briki et al, 2012;Jones & Harwood, 2008;Taylor & Demick, 1994). Such is the case in team sports, where qualitative (Jones & Harwood, 2008) or experimental (Den Hartigh et al, 2020) research has identified scoring as a major determinant of the development of psychological momentum. Especially, dramatic changes in the score, which are sometimes observed in football, are often associated with the most beneficial consequences for the team that is catching up from behind and the most catastrophic for the team that is losing the lead (see for example https://en.wikipedia.org/wiki/Last-minute_goal).…”
Section: Introductionmentioning
confidence: 99%
“…Mood is a state of mind, reflecting the way athletes are feeling at a particular moment. In addition to mood, self-efficacy and motivation may be measured in a straightforward way, just by asking how confident athletes are in their abilities to perform, and how motivated they are at that moment (cf., Den Hartigh et al, 2016 , 2020 ; Vallerand et al, 1988 ). These variables can be measured at a relatively high frequency (e.g.…”
Section: Implementing a Multidisciplinary Dynamic Personalized Perspe...mentioning
confidence: 98%